Analysis of the Transformerless Boost dc-dc Converter with High Voltage Gain in Different Operating Modes and Critical Inductance Calculations - Ebrahim Babaei; Azadeh Mofidi; Sara Laali (Institute of Advanced Engineering and Science, 2015)
In the high voltage dc-dc boost converters, the energy transmission modes are divided into continuous conduction mode (CCM) and discontinuous conduction mode (DCM). In addition, these modes are also divided into two different modes: complete inductor supply mode (CISM) and incomplete inductor supply mode (IISM). In this paper, the operation of the boost dc-dc converter with high voltage gain is analyzed. Firstly, the energy transmission process between CCM and DCM is analyzed. Then, this process is investigated between IISM and CISM. Moreover, the critical inductance between CCM and DCM in addition to CISM and IISM is calculated. Finally, in order to verify the presented theoretical issues, the simulation results in EMTDC/PSCAD software program are used.